2016
DOI: 10.3892/ol.2016.5304
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of PDIA3 and its association with cancer cell proliferation and poor prognosis in hepatocellular carcinoma

Abstract: The prognosis of hepatocellular carcinoma (HCC) is unfavorable following complete tumor resection. The aim of the present study was to identify a molecule able to predict HCC prognosis through comprehensive protein profiling and to elucidate its clinicopathological significance. Comprehensive protein profiling of HCC was performed by liquid chromatography-tandem mass spectrometry. Through the bioinformatic analysis of proteins expressed differentially in HCC and non-HCC tissues, protein disulfide-isomerase A3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…In this study, we used a gel‐free LC–MS‐based proteomics approach to examine the functional effects of collagen from soft‐shelled turtle on human skin. Although spectral counting may not accurately reflect the quantity information, it is useful and has been used in many studies, including those searching for novel diagnostic biomarkers . We were able to successfully identify several proteins whose expression levels were changed >2‐fold in HaCaT cells by the administration of collagen using a semiquantitative method based on spectral counting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a gel‐free LC–MS‐based proteomics approach to examine the functional effects of collagen from soft‐shelled turtle on human skin. Although spectral counting may not accurately reflect the quantity information, it is useful and has been used in many studies, including those searching for novel diagnostic biomarkers . We were able to successfully identify several proteins whose expression levels were changed >2‐fold in HaCaT cells by the administration of collagen using a semiquantitative method based on spectral counting.…”
Section: Discussionmentioning
confidence: 99%
“…Although spectral counting may not accurately reflect the quantity information, 36 it is useful and has been used in many studies, including those searching for novel diagnostic biomarkers. [37][38][39][40][41][42] We were able to successfully identify several proteins whose expression levels were changed >2-fold in HaCaT cells by the administration of collagen using a semiquantitative method based on spectral counting. To examine the role of these identified proteins, we performed GO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency of PDIA3-STAT3 complex formation is a marker of poor prognosis and increases resistance to radiotherapy in laryngeal cancer through modulation of STAT3 activity (19). We have previously reported that the PDIA3 expression levels in HCC tissues are higher than those in adjacent non-cancerous tissues, and that they are associated with overall survival time (20). However, the biological role of PDIA3 in HCC remains unclear.…”
Section: Downregulation Of Protein Disulfide-isomerase A3 Expression mentioning
confidence: 99%
“…Reports have shown that PDIA3 levels were high in the sera of patients with HCC as well as in HCC tissues compared to those in healthy liver or nontumors. (27,28) Interestingly, we found that PDIA3 is also oxidatively modified in HCC cells under high ROS levels, resulting in its redistribution and changes in its function. Among the oxidative modifications of PDIA3, we found that modification of M338 is important for changes in PDIA3 functions.…”
Section: Discussionmentioning
confidence: 83%